The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.5811/westjem.2020.3.44844
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of Driving after Prescription Opioid Use in an Adult ED Sample

Abstract: Introduction Prescription opioid use and driving is a public health concern given the risks associated with drugged driving, but the issue remains under-studied. We examined the prevalence and correlates of driving after taking prescription opioids (DAPO) among adults seeking emergency department (ED) treatment. Methods Participants (aged 25–60) seeking ED care at a Level I trauma center completed a computerized survey. Validated instruments measured prescription opioid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 59 publications
(80 reference statements)
0
1
0
Order By: Relevance
“…13,14 In contrast, a recent US study showed a prevalence as high as 30.8% of current opioid use among ED patients, which is in line with the higher rates of opioid-related harm in the United States as compared to most European countries. 8,27 With a prevalence rate of prescription opioid use of 15% our findings are somewhat in the middle and warrant further studies into the role of the ED in the ongoing opioid epidemic.…”
Section: Patient Characteristics Associated With Misuse and Oudmentioning
confidence: 75%
“…13,14 In contrast, a recent US study showed a prevalence as high as 30.8% of current opioid use among ED patients, which is in line with the higher rates of opioid-related harm in the United States as compared to most European countries. 8,27 With a prevalence rate of prescription opioid use of 15% our findings are somewhat in the middle and warrant further studies into the role of the ED in the ongoing opioid epidemic.…”
Section: Patient Characteristics Associated With Misuse and Oudmentioning
confidence: 75%